The importance of knowing the home conditions of patients receiving long-term oxygen therapy - Godoy, Ilda de [UNESP]; Tanni, Suzana Erico [UNESP]; Hernandez, Carme; Godoy, Irma de [UNESP] (Dove Medical Press Ltd, 2012)
Purpose: Long-term oxygen therapy (LTOT) is one of the main treatments for patients with chronic obstructive pulmonary disease. Patients receiving LTOT may have less than optimal home conditions and this may interfere with treatment. The objective of this study was, through home visits, to identify the characteristics of patients receiving LTOT and to develop knowledge regarding the home environments of these patients.Methods: Ninety-seven patients with a mean age of 69 plus or minus 10.5 years were evaluated. This study was a cross-sectional descriptive analysis. Data were collected during an initial home visit, using a questionnaire standardized for the study. The results were analyzed retrospectively.Results: Seventy-five percent of the patients had chronic obstructive pulmonary disease, and 11% were active smokers. The patients' mean pulse oximetry values were 85.9% plus or minus 4.7% on room air and 92% plus or minus 3.9% on the prescribed flow of oxygen. Most of the patients did not use the treatment as prescribed and most used a humidifier. The extension hose had a mean length of 5 plus or minus 3.9 m (range, 1.5-16 m). In the year prior to the visit, 26% of the patients received emergency medical care because of respiratory problems. Few patients reported engaging in leisure activities.Conclusion: The home visit allowed us to identify problems and interventions that could improve the way LTOT is used. The most common interventions related to smoking cessation, concentrator maintenance and cleaning, use of a humidifier, and adjustments of the length of the connector hose. Therefore, the home visit is a very important tool in providing comprehensive care to patients receiving LTOT, especially those who show lack of adequate progress and those who show uncertainty about the treatment method.
Keywords: LTOT; home visits; chronic obstructive pulmonary disease (COPD); treatment compliance